Enhancing Economic and Legal Frameworks for Artificial Intelligence Technologies in Remote Education - Gubarev , Ruslan; Biletska, Halyna; Mironova , Nataliia; Kazanishena, Natalia; Skrypnyk , Serhii; Mashtakova , Nataliia (Journal of Ecohumanism, 2024)
In essence, enhancing economic and legal frameworks for artificial intelligence technologies in remote education is a multifaceted endeavor that requires concerted efforts from all stakeholders. By focusing on educator training, equitable access, adaptable legal regulations, ethical development practices, sustainable economic models, international collaboration, private sector involvement, public transparency, and continuous evaluation, we can create an educational environment where artificial intelligence serves as a powerful tool for learning. Such an environment not only improves educational outcomes but also prepares students to navigate and contribute to a world increasingly shaped by advanced technologies. This paper explores vital improvements in the economic and legal frameworks governing the application of artificial intelligence technologies within distance learning. The focus of the study is on how these regulations are shaped and implemented. The main objective is to develop a methodological approach that enhances these frameworks. The research utilizes the IDEF0 methodology to propose a functional model that refines the economic and legal controls of artificial intelligence use in remote education settings. Innovations within the IDEF0 model segments are discussed, aiming to bolster these frameworks effectively. Future research directions are suggested, including the integration of socio-psychological factors.